Theoretical and methodological bases of formation of the professional-pedagogical culture of the future elementary school teacher (Pedagogy of Higher and Secondary Education, 2012)
I. V. Onyshchenko.Theoretical and methodological bases of formation of the professional-pedagogical culture of the future elementary school teacher.The article explains the purpose of vocational and educational culture of primary school teacher, its structure, established psychological and pedagogical conditions and stages of formation technology professional and pedagogicalculture of the future primary school teacher.
Keywords: professional culture; professional and pedagogical culture; primary school teacher